DIFFERENCES IN FOLKLORE BETWEEN SANGKURIANG (INDONESIA) AND THE OEDIPUS (GREECE) (A COMPARATIVE STUDY) - Mutmainnah (Bajang Institute, 2021)
Every country has its own folklores, whether they are true stories or just fairy tales. The world consists of folklore from a different country but has a similar folklore story. One of them is Sangkuriang a folklore from Indonesia and The Oedipus Greece. This study aims to determine how the similarities and differences of the two folklores are. In analyzing this research, the author uses two approaches. The first is Greimas’ structural theory to analyze the structure of the folklore. And the second is a literary comparison approach. The result of this study indicated that there was both similarities and differences of story structure. There are similarities and differences in the structure of the story between Sangkuriang and The Oedipus. However, both not influence and influenced by another, because Sangkuriang represented of his own country, likewise of The Oedipus.